Optimization of simultaneous multislice EPI for concurrent functional perfusion and BOLD signal measurements at 7T. Issue 1 (28th July 2016) - Ivanov, Dimo; Poser, Benedikt A; Huber, Laurentius; Pfeuffer, Josef; Uludağ, Kâmil
Abstract : Purpose: To overcome limitations of previous ultra‐high‐field arterial spin labeling (ASL) techniques concerning temporal resolution and brain coverage by utilizing the simultaneous multi‐slice (SMS) approach. Methods: An optimized, flow‐alternating inversion recovery quantitative imaging of perfusion using a single subtraction II scheme was developed that tackles the challenges of 7 tesla (T) ASL. The implementation of tailored labeling radiofrequency pulses reduced the effect of transmit field ( B 1 + ) inhomogeneities. The proposed approach utilizes an SMS echo‐planar imaging (EPI) readout to efficiently achieve large brain coverage. Results: A pulsed ASL (PASL) technique with large brain coverage is described and optimized that can be applied at temporal resolutions below 2.5 s, similar to those achievable at 1.5 and 3T magnetic field strength. The influences of within‐ and through‐slice acceleration factors and reconstruction parameters on perfusion and blood‐oxygenation‐level‐dependent (BOLD)‐signal image and temporal signal‐to‐noise ratio (SNR) are presented. The proposed approach yielded twice the brain coverage as compared to conventional PASL at 7T, without notable loss in image quality. Conclusion: The presented SMS EPI PASL at 7T overcomes current limitations in SNR, temporal resolution, and spatial coverage for functional perfusion and BOLD signal as well as baseline perfusion measurements. Magn Reson Med 78:121–129, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution‐NonCommercial‐NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non‐commercial and no modifications or adaptations are made.